Efficacy of raman spectroscopy in the diagnosis of kidney cancer: A systematic review and meta-analysis. Issue 27 (2nd July 2020) - Jin, Hongyu; He, Xiao; Zhou, Hui; Zhang, Man; Tang, Qingqing; Lin, Lede; Hao, Jianqi; Zeng, Rui
Abstract: Objective: To comprehensively analyze the relative effectiveness of Raman spectroscopy (RS) in the diagnosis of suspected kidney cancer. Patients and methods: We performed a complete systematic review based on studies from PubMed/Medline, EMBASE, Web of Science, Ovid, Web of Knowledge, Cochrane Library and China National Knowledge Infrastructure. We identified 2413 spectra with strict criteria in 6 individual studies published between January 2008 and November 2018 in accordance to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. We summarized the test performance using random effects models. Results: General pooled diagnostic sensitivity and specificity of RS to kidney cancer were 0.96 (95% confidence interval [CI] 0.95–0.97) and 0.91 (95% CI 0.89–0.92). The pooled positive likelihood ratio (LR) was 9.57 (95% CI 5.73–15.46) while the negative LR was 0.04 (95% CI 0.02–0.11). The pooled diagnostic odds ratio was 238.06 (95% CI 77.79–728.54). The area under curve of summary receiver operator characteristics was 0.9466. Conclusion: Through this meta-analysis, we found a promisingly high sensitivity and specificity of RS in the diagnosis of suspected kidney masses and tumors. Other parameters like positive LR, negative LR, diagnostic odds ratio and area under curve of the summary receiver operator characteristics curve all helped to illustrate the high efficacy of RS in the diagnosis of kidney cancer.